1-Cyclohexyl-3-{(E)-[1-(pyridin-2-yl)- ethylidene]amino}thiourea - Fasihuddin B., Ahmad; Md. Abdus, Salam; Md. Abu, Affan; Edward R. T., Tiekink; Seik Weng, Ng (International Union of Crystallography, 2011)
In the title thiourea derivative, C14H20N4S, the non-ring non-H atoms are approximately planar, with an r.m.s. deviation of 0.0720 A˚ . The pyridine ring is twisted out of this plane and makes a dihedral angle of 16.85 (13) with it. The mean plane passing through the cyclohexyl ring is almost normal to the central plane [dihedral angle = 69.23 (8)]. An intramolecular N—HN(imine) hydrogen bond occurs. Centrosymmetric dimers are formed in the crystal structure via pairs of N—HS hydrogen bonds, and these are connected into a supramolecular chain along the a axis via C—H(pyridyl) interactions. Related li